Sosialisasi Undang-Undang Informasi Transaksi Elektronik Kepada Siswa SMAN 1 Gunung Toar Kabupaten Kuantan Singingi - Muhammad Iqbal; Afrinald Rizhan; Aprinelita Aprinelita; Ita Iryanti; Halmadi Asmara; sahri muharam; shilvi richiyanti (BHAKTI NAGORI (Jurnal Pengabdian kepada Masyarakat), 2021)
Law Number 11 of 2008 concerning Electronic Transaction Information is a regulation that is often in direct contact with various groups of people in this advanced technology era. In general, the ITE Law has not been well socialized among high school students, especially SMAN 1 Gunung Toar, due to various factors, one of which is the lack of student understanding of the existing laws and regulations. As for the material in the Community Service material at SMAN 1 Gunung Toar, among others: What is the ITE Law, Am I covering the actions regulated in the ITE Law, what actions and sanctions are given to the perpetrators ITE Law criminal